Replication of Hamel & Wilcox-Archuleta (2022): "Black Workers in White Places: Daytime Racial Diversity and White Public Opinion" - Jeremy Gretton; Tobias Roemer; Elmar Schlüter (Institute for Replication (I4R), 2024)
In this replication study, we revisit the main empirical claims of Hamel and Wilcox-Archuleta's (HW) 2022 study on the impact of daytime racial diversity on White Americans' voting behavior and racial attitudes. HW introduce a novel zip code level measure of racial diversity that accounts for the influx of Black workers during daytime, showing that conventional purely residential based measures often underestimate the true degree of experienced racial diversity. Using survey data from the CCES, their findings suggest a negative correlation between racial flux and White Americans' Democratic voting tendencies and a positive correlation with racial resentment and opposition to affirmative action, all while controlling for the residential share of Blacks in the zip code. We assess the replicability of these findings by: (1) replicating the main results using the provided replication code, (2) reconstructing the racial flux measure and survey from raw data, (3) conducting multiverse analyses, and (4) replicating the analysis using an alternative data source. Our replication validates the robustness and accuracy of HW's initial conclusions, emphasizing the role of daytime racial diversity in shaping White Americans' political and racial attitudes.
Keywords: D72; J15; 330; Racial Diversity; Racial Attitudes; Voting Behavior